STRATEGI KOMUNIKASI PT. ANDALAN MITRA PRESTASI PADANG DALAM MEREKRUT CALON TENAGA KERJA INDONESIA - ULFAH, DINI; WIRMAN, WELLY (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Negative news about the migrant workers abroad so much grown invarious media that makes a job as a migrant worker as a scary thing for somepeople. to overcome this we need a way or solution in order to work as migrantworkers are no longer considered to be a scary thing. efforts that can be done by.Mainstay Partners Achievement Padang as Prospective migrant recruiter includemaking communication to the public. In the communication must have certainstrategies in order to achieve the desired goal. This study aims to determine howthe communication strategy of PT. Andalan Mitra Prestasi Padang in theIndonesian Labor candidate recruiting and what are the factors - factorssupporting and inhibiting the Indonesian Labor candidate recruiting.This research was conducted in PT. Andalan Mitra Prestasi Padang Jl. No.Lt. S.Parman. 81-82B Padang, West Sumatra. This study used a qualitativedescriptive method using a model of interactive data analysis and HubermenMiles. Data - the data obtained were then processed for reduction, served toproduce a general conclusion.From the results of the study showed that the communication strategy byPT. Andalan Mitra Prestasi Padang Achievement in recruiting candidates amongmigrant workers through persuasive and educative approach, cooperation,coordinative and integrative, the Internet, and flyers. The supporting factors inrecruiting candidates TKIs is the existence of the Mobilization Permit (SIP), JobOrder and Demand Letter, facilities and infrastructure such as service vehicles, theinfo TKI successful, communicators who have credibility in the field ofemployment and placement workers and inhibiting factors, among others, is thepresence of negative issues, public ignorance, and lack of family consent.Keyword: communication, communication strategy, and recruitment